2016
DOI: 10.1017/s0021932016000468
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of Stigma and Discrimination in Health Care Settings Towards Sub-Saharan African Migrant Women Living With Hiv/Aids in Belgium: A Qualitative Study

Abstract: SummaryStigma and discrimination within health care settings remain a public health challenge across diverse cultural environments and may have deleterious effects on mental and physical health. This study explores the causes, forms and consequences of HIV-related stigma and discrimination among migrant sub-Saharan African women living with HIV in Belgium. A qualitative study was conducted with 44 HIV-positive sub-Saharan African migrant women between April 2013 and December 2014 in health care settings in Bel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
44
0
6

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(53 citation statements)
references
References 67 publications
1
44
0
6
Order By: Relevance
“…The patients tended to minimize and justify unprofessional behaviors, even blaming themselves for nurses' inappropriate behaviorstoward them. The confirmation of perceived discrimination indicates that the interaction between MPs and their care providers presents problems [44] that should be analyzed in greater depth.…”
Section: Discussionmentioning
confidence: 90%
“…The patients tended to minimize and justify unprofessional behaviors, even blaming themselves for nurses' inappropriate behaviorstoward them. The confirmation of perceived discrimination indicates that the interaction between MPs and their care providers presents problems [44] that should be analyzed in greater depth.…”
Section: Discussionmentioning
confidence: 90%
“…Stigma and negative attitudes toward PLWH by health care providers can manifest in poor patient-provider relationships and denial of proper care (8, 1015), and continue to be a focus of stigma interventions (1622). Stigma and discrimination are also directed toward providers who treat HIV patients (23) and can perpetuate an unwillingness to treat PLWH.…”
Section: Introductionmentioning
confidence: 99%
“…Stigma and discrimination has also been found associated with a decreased willingness to disclose one’s HIV status, which in turn may lead to depression and anxiety (2, 2427). Stigma and discrimination in health care settings lead to PLWH hiding their HIV status from providers (8, 27, 28), creating a primary barrier to HIV testing (7, 12, 29, 30) and care-seeking (7, 10, 31). A meta-analysis of global studies published between 1996 and 2013 found that people who had experienced HIV-related stigma were at greater risk of depression, lower social support, and “were 21% less likely to access or use health and social services” (32).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In many countries, PLWH are subjected to HIV-related stigma and discrimination (11,12,13). Although Turkey has a similar trend (14,15), there are few studies on PLWH's perception of their diagnosis and treatment, their relationship with healthcare workers and other professionals, and their experiences in healthcare environments.…”
Section: Introductionmentioning
confidence: 99%